Effect of genotype and age on cerebral [F-18]FDG uptake varies between transgenic APP(swe)-PS1(dE9) and Tg2576 mouse models of Alzheimer's disease - Anniina Snellman; Jatta S. Takkinen; Francisco R. López-Picón; Olli Eskola; Olof Solin; Juha O. Rinne; Merja Haaparanta-Solin (NATURE PUBLISHING GROUP, 2022)
Back-translation of clinical imaging biomarkers of Alzheimer's disease (AD), such as alterations in cerebral glucose metabolism detected by [F-18]FDG positron emission tomography (PET), would be valuable for preclinical studies evaluating new disease-modifying drugs for AD. However, previous confounding results have been difficult to interpret due to differences in mouse models and imaging protocols between studies. We used an equivalent study design and [F-18]FDG mu PET imaging protocol to compare changes in cerebral glucose metabolism in commercial transgenic APP(swe)-PS1(dE9) (n = 12), Tg2576 (n = 15), and wild-type mice (n = 15 and 9). Dynamic [F-18]FDG scans were performed in young (6 months) and aged (12 or 17 months) mice and the results verified by ex vivo methods (i.e., tissue counting, digital autoradiography, and beta-amyloid and Iba-1 immunohistochemistry). [F-18]FDG uptake exhibited significant regional differences between genotypes (TG < WT) and ages (6 months <12 months) in the APP(swe)-PS1(dE9) model, whereas similar differences were not present in Tg2576 mice. In both models, only weak correlations were detected between regional beta-amyloid deposition or microgliosis and [F-18]FDG uptake. By using equivalent methodology, this study demonstrated differences in cerebral glucose metabolism dysfunction detected with [F-18]FDG PET between two widely used commercial AD mouse models.